If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -5) = 4(x + 15) Reorder the terms: 3(-5 + 3x) = 4(x + 15) (-5 * 3 + 3x * 3) = 4(x + 15) (-15 + 9x) = 4(x + 15) Reorder the terms: -15 + 9x = 4(15 + x) -15 + 9x = (15 * 4 + x * 4) -15 + 9x = (60 + 4x) Solving -15 + 9x = 60 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -15 + 9x + -4x = 60 + 4x + -4x Combine like terms: 9x + -4x = 5x -15 + 5x = 60 + 4x + -4x Combine like terms: 4x + -4x = 0 -15 + 5x = 60 + 0 -15 + 5x = 60 Add '15' to each side of the equation. -15 + 15 + 5x = 60 + 15 Combine like terms: -15 + 15 = 0 0 + 5x = 60 + 15 5x = 60 + 15 Combine like terms: 60 + 15 = 75 5x = 75 Divide each side by '5'. x = 15 Simplifying x = 15
| h=2(-2)3 | | 2x^2+27x+62=0 | | h=2(2)+4 | | 2x+3x=1800 | | 1=0.2x-0.6-7 | | h=2(1)+4 | | 8y-17=10y | | 576v^2+1=-48v | | h=2(-2)+4 | | 2x^2+27+62=0 | | 4(3x+28)=5(x+28) | | h=2(-3)+4 | | M+8+14=31 | | 8u-16=-3(u+9) | | -4w-9=2(5x+9) | | g3=1/8 | | 63-x=35-8x | | 8b-2b-4=6 | | 7x-11-3x=3x+19 | | 44x+2(5x-6)=-3x-39 | | (5x-2)5= | | 24n-10n+36= | | 10z-z=3+3z-3-12 | | 47g^2+50g=0 | | 7[x+(-11)]+(-3)=-53 | | X*11=35 | | 6x-108/5=2x | | -31+8x=29+6x | | y=29-4(6) | | 4sin^2x+2=5 | | y=29-4(5) | | X(3x+2)=23 |